FROM HOPE TRIAL TO ONTARGET TRIAL: THE «HOPE» TO REACH THE «TARGET» - TO IMPROVE PROGNOSIS IN HIGH RISK PATIENTS - Yu. M. Lopatin (Столичная издательская компания, 2016)
Results of HOPE trial are analyzed. It is noted, that treatment with angiotensine converting enzyme inhibitor (iACE) ramipril improves the prognosis in high risk cardio-vascular patients. The objectives and study design of ONTARGET/TRANSCEND trials are introduced. Perspectives of joint use of ACE inhibitor and antagonist of angiotensin II receptor are discussed.